Diagnosis of human herpesvirus 6B primary infection by polymerase chain reaction in young children with exanthematic disease Diagnóstico de infecção primária pelo herpesvírus humano tipo 6B através da técnica de reação em cadeia da polimerase em crianças com doença exantemática - Ivna de Melo Magalhães; Rebeca Vasquez Novo Martins; Renata Oliveira Vianna; Solange Artimos Oliveira; Silvia Maria Baeta Cavalcanti (Revista da Sociedade Brasileira de Medicina Tropical, 2011)
INTRODUCTION: Exanthem subitum is a classical rash disease of early childhood caused by human herpesvirus 6B (HHV-6B). However, the rash is frequently misdiagnosed as that of either measles or rubella. METHODS: In this study, a nested multiplex polymerase chain reaction (PCR) was used to diagnose HHV-6B primary infection, differentiate it from infections caused by HHV-6A and compare it to antibody avidity tests. The samples were separated into case group and control group according to the results of the indirect immunofluorescence assay (IFA) technique. RESULTS: From the saliva samples analyzed, HHV-6A DNA was detected in 3.2% of the case group and in 2.6% of the control group. Regarding HHV-6B, PCR detected viral DNA in 4.8% of the case group and in 1.3% of the control group. Among the serum samples studied, a frequency of 1.7% was determined for HHV-6A in the case group and 1.2% in the control group. PCR did not detect HHV-6B DNA in serum samples. The sensitivity and specificity of the PCR technique ranged from 0% to 4.8% and 97.5% to 100%, respectively, compared to IFA. CONCLUSIONS: The PCR technique was not suitable for diagnosing primary infection by HHV-6B in children with exanthematic disease and should not substitute the IFA. INTRODUÇÃO: O exantema súbito é uma doença comum durante a infância e pode ser causada pela infecção por herpesvirus humano tipo 6B (HHV-6B). No entanto, a erupção cutânea característica dessa doença, é frequentemente confundida com outras viroses como sarampo ou rubéola. MÉTODOS: Foi utilizada a técnica de reação em cadeia da polimerase (PCR) no formato nested multiplex para o diagnóstico de infecção primária por HHV-6B, diferenciação entre as infecções causadas pelo HHV-6A e comparação com testes de avidez de anticorpos. As amostras foram separadas em grupo caso e grupo controle, de acordo com os resultados do teste de imunofluorescência indireta (IFA). RESULTADOS: Nas amostras de saliva analisadas, o DNA do HHV-6A foi detectado em 3,2% no grupo caso e em 2,6% das amostras do grupo controle. Em relação ao HHV-6B, o DNA viral foi observado em 4,8% no grupo caso e em 1,3% no grupo controle. Após a realização da PCR nas amostras de soro, o DNA do HHV-6A foi detectado em 1,7% no grupo caso e em 1,2% no grupo controle, enquanto o DNA do HHV-6B não foi detectado. A sensibilidade e a especificidade da técnica de PCR variaram de 0% a 4,8% e de 97,5% a 100%, respectivamente, quando comparado com a IFA. CONCLUSÕES: A técnica de PCR não se mostrou adequada para o diagnóstico de infecção primária pelo HHV-6B em crianças com doença exantemática e não deve substituir a IFA.